Anesthetic Management in Patient with Traumatic Brain Injury undergoing Elective Spinal Surgery - Soedibjo, Dennis Prakas; Harahap, Mohamad Sofyan; Gaus, Syafruddin (Jurnal Neuroanestesi Indonesia, 2026)
The incidence of traumatic brain injury that concurrent with injuries such us traumatic spinal injuries is relatively high. When considering anesthetic management for patients with acute traumatic brain injury undergoing non-brain surgery procedures, understanding of the implications of traumatic brain injury on anesthesia management is essential for achieving favorable surgical results while minimizing the risk of secondary brain injury to ensure patient safety and optimal outcomes. We report a case of a 25 years old man who presented with decrease of consciousness 3 days prior admission to the hospital after sudden fall in the bathroom. Complaints were accompanied with vomiting, weakness and paresthesia in both bilateral upper extremities and lower extremities. Supportive examination revealed an epidural hematoma at regio frontoparietal sinistra, minimal subdural hematomas at regio anterior falx cerebelli and bilateral tentorium cerebelli, subgaleae hematomas at regio bilateral parietal, with multiple cervical fracture at the C5 level with associated cervical canal narrowing. Due to the minor intracranial bleeding with no significant symptoms for days, patient then scheduled for elective C4-C6 laminectomy and posterior stabilization surgery. Anesthesia management for patient with traumatic brain injury that undergoes non-brain surgery comes with challenges, mainly on how to prevent secondary brain injury and minimizing complications. Comprehensive perioperative planning and vigilant monitoring are essential to ensure patient safety and optimal outcomes